INTEGRATION OF DIGITAL TECHNOLOGIES IN ADULT EDUCATION: DIGITAL COMPETENCE OF SCIENTIFIC AND PEDAGOGICAL STAFF OF HIGHER EDUCATION INSTITUTIONS (Physical Culture and Sport: Scientific Perspective, 2024)
The review article pays special attention to the development of digital competence of scientific and pedagogical workers of higher education institutions to ensure the successful integration of digital technologies into the educational process. The main trends and challenges that accompany the introduction of digital technologies into adult education are considered. The importance of the use of digital technologies by teachers of higher education institutions is emphasized, as well as the rapid development of information technologies, which affects the educational process of higher education institutions, and the digital competence of scientific and pedagogical workers is a necessary component of their professional activities. The use of digital technologies by scientific and pedagogical staff of higher education institutions over the past five years has been analyzed. The impact of the rapid development of information technologies on the educational process is highlighted, it is proven that the digital competence of scientific and pedagogical workers is a necessary component of their professional activities, plays a huge role in modern education and consists of such aspects as ensuring access to information, developing new teaching methods, improving the quality of teaching, and preparing for a future career. It has been proven that today in adult education, without digital competence, a teacher and a student will not be able to achieve the expected effectiveness of their activities, in particular, understanding the essence of the tasks and the problems being solved; gaining experience in their field; the ability to choose means and methods of activity adequate to the specific circumstances of place and time; a sense of responsibility for the results obtained; the ability to learn from mistakes and make adjustments in the process of achieving the goal; resistance to stress and failures, their prediction and avoidance in work and life.
Keywords: digital technologies; integration; adult education; scientific and pedagogical workers; higher education institutions; digital competence